2020
DOI: 10.35137/jei.v21i2.436
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kepuasan Kerja Karyawan Pt Astra International Daihatsu, TBK Cabang Narogong

Abstract: The purpose of this study was to determine the effect of compensation and work discipline on job satisfaction of employees PT. Astra International Daihatsu, Tbk Narogong. The research method uses qualitative and quantitative descriptive analysis, the analysis model used is linear regression both simply and multiple. The study population of all employees of PT. Astra International Daihatsu, Tbk Narogong with 93 employees. The technique used is simple random sampling using Slovin formula obtained a sample of 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…The results of this study align with research by Susanti & Aesah (2022) and Lumentut & Dotulong (2015), concluding that there is no impact of work discipline on job satisfaction. However, this contradicts the findings of Djari & Sitepu (2017), Widiyanto & Setyawasih (2019), Putri et al (2020), Putri & Kustini (2021), who concluded that work discipline affects job satisfaction.…”
Section: Impact Of Work Discipline On Job Satisfactionmentioning
confidence: 65%
“…The results of this study align with research by Susanti & Aesah (2022) and Lumentut & Dotulong (2015), concluding that there is no impact of work discipline on job satisfaction. However, this contradicts the findings of Djari & Sitepu (2017), Widiyanto & Setyawasih (2019), Putri et al (2020), Putri & Kustini (2021), who concluded that work discipline affects job satisfaction.…”
Section: Impact Of Work Discipline On Job Satisfactionmentioning
confidence: 65%
“…The better the compensation provided, the greater the employee's job satisfaction. The influence of compensation on job satisfaction is explained through empirical studies, research conducted by Rahayu & Pramularso (2019), Rahayu & Pramularso (2019), Herdiansah (2017), Siregar & Pasaribu (2022), Wiyantini (2016), andParimita et al (2018) state that compensation has a positive and significant influence on job satisfaction.…”
Section: Compensation and Job Satisfactionmentioning
confidence: 99%
“…In contrast to research conducted by Alonderiene & Majauskaite (2016) which states that transformational leadership has an insignificant influence on job satisfaction. The effect of compensation on job satisfaction is explained through empirical studies, research conducted by Rahayu & Pramularso (2019), Fauzi (2017), Herdiansah (2017), Herawati & Ermawati (2020), Wiyantini (2016) and Retnoningsih et al (2016) state that compensation has a positive and significant influence on job satisfaction. The influence of organizational culture on job satisfaction is explained through empirical studies, research conducted by Abror (2022), Wambui (2018), Qazi et al (2017) and Lund (2003) stated that organizational culture had a significant influence on job satisfaction, in contrast to research conducted by Shah (2015) stated that organizational culture had an insignificant influence on job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In the current age of intense global competition, businesses need their staff to perform at a high level in order to thrive. This may be accomplished by fostering harmonious relationships inside the organisation to resolve differences in interests and prevent conflicts that might hurt both parties (Suwandi et al, 2021;Yeremia et al, 2022;Wijayanto et al, 2020). According to assessments of providing needs and ensuring satisfaction, the compensation gap is still not in line (Askiyanto et al, 2023;Lestari et al, 2020;Nguyen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the company's offerings, human labour plays the most crucial role in creating high-quality and fulfilling items. Because of this, the organisation has abundant natural human resources (Wijayanto et al, 2020;Dessler, 2017).…”
Section: Introductionmentioning
confidence: 99%